Biomineralization Directed by Prenucleated Calcium and Phosphorus Nanoclusters Improving Mechanical Properties and Osteogenic Potential of Antheraea pernyi Silk Fibroin‐Based Artificial Periosteum. Issue 8 (15th March 2021) - Shuai, Yajun; Lu, Huan; Lv, Ruyin; Wang, Jie; Wan, Quan; Mao, Chuanbin; Yang, Mingying
Abstract: The use of biomacromolecules as templates to control the nucleation and growth of hydroxyapatite crystals to prepare bioactive materials is a valuable approach in bone tissue engineering. Here, an artificial periosteum is prepared by biomineralizing Antheraea pernyi fibroin ( AF ) membrane with prenucleated nanoclusters, which can promote the osteogenic differentiation of mesenchymal stem cells (MSCs) and induce the formation of bone matrix protein in vivo. To achieve this, a biologically inspired prenucleated calcium and phosphorus nanocluster mineralization system is designed to nucleate and generate hydroxyapatite crystals on the surface of the AF membrane. This biomineralization process provides AF membranes with improved elastic modulus and tensile strength. Subsequently, cell viability assay, hemolysis test, and H&E staining show that the mineralized AF ( MAF ) membranes has good cytocompatibility, hemocompatibility, and histocompatibility in vitro and in vivo. Additionally, the MAF membranes significantly promote osteogenic differentiation of MSCs in the absence of osteogenic inducer in vitro. Experiments in vivo demonstrate that bone‐related matrix proteins are highly expressed in MAF groups with or without MSCs seeded. Therefore, the use of bioinspired prenucleated nanoclusters to prepare artificial periosteum based on biomineralized AF membrane is a promising strategy in the field of bone tissue engineering. Abstract : A biologically inspired mineralization method based on amorphous calcium phosphate nanocluster is invented and used for the growth of hydroxyapatites on the A. pernyi fibroin ( AF ) membrane. After biomineralization, AF membranes not only have good cytocompatibility, hemocompatibility, and histocompatibility but can also induce the osteogenic differentiation of mesenchymal stem cells in vitro and promote the formation of bone‐related matrix proteins in vivo.